Relationship Pattern Of Working Parents To The Independence Of Toilet Training Pre School Children (Literature Study) - Suci Fitri Rahayu (MBUnivPress, 2021)
The success of toilet training occurs because there are many factors including age, sex, culture, parents' motivation, children's readiness physically, psychologically and intellectually. In addition, one of the important factors for the success of toilet training is the parenting style applied by parents in educating their children at home. This study aims to determine the relationship between working parents' parenting styles and children's independence in toilet training. In this study, a literature study was used by analyzing 5 national journals and 2 international journals. This research study is a type of literature study research by looking for theoretical references that are relevant to the cases or problems found. Based on the results of the analysis of several journals above, there are many who say that the parenting style of working parents is related to children's independence in toelite trening. The results of the research can be used as material to evaluate and prepare health promotion strategies for health workers, especially nurses, in increasing the knowledge and attitudes of parents, especially parents who work outside the home to apply parenting to pre-school children (3 - 5 years) according to the child's personality development. Keywords: parenting style, toilet training